ATTITUDES TOWARD STATISTICS IN MIDDLEAGED PERUVIAN COLLEGE STUDENTS - Tarazona Vargas, Enver (2013)
This paper studies the attitudes of college students concerning statistics; students who aretaking the basic course in Statistics under an Adult Worker Student program at a private university in Lima, Peru. Two scales have been considered: Attitudes Toward Statistics (ATSE) proposed byEstrada (2002) and Attitudes Toward Statistics (ATSC) proposed by Cazorla et al (1999).The sample corresponds to 137 students with ages ranging from 32 to 42 years old, fromfour engineering majors, , 84% male and 52% who had taken a previous course in statistics.The item analysis was performed considering the Classical Test Theory (CTT) and ItemResponse Theory (IRT) under the Bayesian inference of the Samejima’s graded response model(Tarazona, 2013).The results reveal that AEC has a reliability of 0.93, and by comparison a shortened versionof AEE after eliminating two items has a reliability of 0.88. Both scales are closely correlated aretherefore are interchangeable. However AEE is the only one that reveals differences by specialty,especially among students of the School of Industrial Engineering (positive attitudes), and ofTelecommunications and Network Engineering (less positive attitudes). Finally, other factors suchas gender, different age groups and experience in a previous course of Statistics were insignificantin explaining attitudes toward statistics at any scale.